Empowerment Women of Mekarmanik Village to Prevent Early through Balai Prima Women's School in 2020-2023 - Sintia Catur Sutantri; Risma Wati; Risalatu Mirajiah (Research Synergy Foundation, 2024)
This research was motivated by the rampant phenomenon of early marriage in Indonesia, which has become a complex and controversial social issue. Early marriage was always associated with beliefs and traditions in a region with diverse cultures and religions. This study analyzes efforts to prevent early marriage in Mekarmanik Village, Cimenyan District, Bandung Regency through women's empowerment. The program used is the Balai Prima girls’ school, which provides non-formal education for adolescent girls aged 13-18 years. This study uses a qualitative descriptive method, focusing on data collection and analysis, to shed light on the phenomenon of early marriage in local social, cultural, and economic contexts. The results show that non-formal education and women's empowerment can increase awareness about women's rights and the risks of early marriage, as well as provide practical skills that aid decision-making. The implementation of this program is in line with the Sustainable Development Goals (SDGs), especially in terms of gender equality and improving the quality of education. Therefore, it is important to address early marriage, which involves education, empowerment, and social change.